Design and Experimental Verification of Pressurized Cylinders in Hydraulic Rubber Hose Pressure Washers - Xiaoxiao Niu; Guangfa Hao; Chengliang Zhang; Lei Li (Actuators, 2021)
Hydraulic rubber hoses are subject to great hydraulic impact during the actual working process, which causes a great potential safety hazard. Therefore, it is necessary to carry out pressure tests on hose assemblies to ensure its quality, so providing a high pressure for the hydraulic hose has become the key technology of this problem. Aiming at solving the problem of detection of pressure resistance in hydraulic rubber hose cleaning machines, this paper analyzed the pressurization mechanism of the hydraulic pressurized cylinder and proposed a method of continuous pressurization. This paper also theoretically analyzed the pressure expansion of the rubber hose, and the conclusion is that for the maximum hose capacity (hose size is Φ25 mm × 6 m), the volume of water required to provide water in the hose from 10 MPa to 100 MPa is 0.59 L. The pressurized cylinder was designed and checked theoretically and analyzed by the finite element method. It is concluded that the maximum stress of the pressurized cylinder is concentrated at the bottom of the high-pressure chamber, and the outlet hole at the bottom of the cylinder barrel of the high-pressure chamber is the weakest part of the pressurized cylinder. The performance of the supercharging cylinder is verified by experiments, which proves the feasibility, rapidity and stability of the supercharging cylinder.